The use of modern learning technologies in training of specialists Information Profile of databases - Dopira, R.I.; Popova, N.V.; Bazikova, K.M.; Ganzer, O. (Вестник Карагандинского университета, 2016)
The article deals with modern learning technology, where the teacher helps students to learn independently, to analyze, organize, assess the acquired knowledge and apply them in their professional activities. The authors provide checklists, compiled on the basis of the pyramid Bloom, criteria and parameters of assessment of practical exercises and project. The project made the subject area chosen development environment and programming language analysis.
Keywords: modern learning technology; Bloom's taxonomy; information system; project; Visual Studio 2010; C# programming language